Effect of sunkist orange peel extract nanoparticle granules on the lipid profile levels in diabetic wistar rat - Mutia, Maya Sari; Harahap, Safriani; Nurhady, Fahira Zahra; Gunawan, Robby; Dewani, Yunita; Chairul, Muhammad; Fadillah, Qori (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
The research was conducted to determine the effect of Sunkist orange (Citrus sinensis (L.) Osbeck) peel extract nanoparticles in granular form on lipid profile levels in alloxan-induced Wistar rats (Rattus norvegicus). The study employed an experimental method with a posttest-only control group design. The population for this research was Wistar rats. The study used five treatment groups, resulting in a total of 25 rats, with five rats in each treatment group, as determined using the Federer formula. After the administration of sunkist orange peel extract nanoparticles at different doses for 14 days, the results showed a decrease in total cholesterol, LDL, triglycerides, and HDL levels. The research findings demonstrated the influence of reducing lipid profile levels in diabetic rats. The effective dose for reducing the lipid profile in this study was found to be 100 mg for total cholesterol, 70 mg for triglyceride, and 70 mg for both HDL and LDL when using the ethanol extract of sunkist orange peel.